Unexpectedly, intense livestock grazing in arid rangelands strengthens the seedling vigor of consumed plants - Tadey, Mariana (2016)
Grazing intensification with non-native livestock is known to degrade vegetation cover, particularly in arid environments where low resource availability strongly limits plant recovery after damage. However, it remains unclear whether the effect of grazing on consumed plants is transmitted to plant offspring. We hypothesized that grazing would reduce fruit weight, germination percentage, and seedling vigor of consumed vegetation. Therefore, we collected mature fruits from six dominant shrub species in seven independent paddocks with increasing livestock densities. Fruits were air-dried and weighed before seed sowing. After seedling emergence, we measured the percentage of germination and seedling vigor, i.e., height and number of leaves. Hierarchical models were used to account for the effects of plant species and year of collection. Results show that, in general, increasing livestock density reduced fruit weight and percentage of germination of consumed plants. However, surprisingly, increasing livestock density enhanced seedling vigor. Overall, increasing livestock density has both negative and positive effects on consumed plantsʼ offspring.